Home advantage in judo: Analysis by the combat phase, penalties and the type of attack - Brito, C. J.; Miarka, B.; Lopez Diaz de Durana, A.; Fukuda, D. H. (Journal of Human Kinetics, 2017)
Previous studies indicate positive home advantage in judo; however, the factors that influence home advantage have yet to be fully explored. This study investigated the potential differences in technical-tactical variables between home and visiting athletes. A total of 1411 video recorded matches were analyzed (123 home, 1288 away) from 36 international judo competitions contested in 2011-12. The matches were analyzed by the following criteria: combat phases (approach, gripping, attack, defense, groundwork and pause), penalties (by the athlete or the opponent) and the types of attacks (with or without a score). Elite judo athletes competing in their home country attacked more frequently using trunk/leg couple techniques (p < 0.011) and scored more frequently with arm/leg couple techniques (p < 0.001), while visiting judo athletes received fewer scores from penalties (p < 0.001) and engaged in more frequent pauses during competition (p < 0.01). The results of this study provide an outline of technical-tactical differences that may contribute to home advantage in judo.